The future of PetMonitor app using scenario building - Domondon, Alvin Bobiles; Imbang, Glen A. (Quezon City, Philippines Technology Management Center, 2014)
Mobile computing enabled mobile technology to evolve. Now mobile technology is more than powering electronic equipments to make and receive calls. Today this technology is used for everyday use, most often in communications, entertainment and office productivity. It has been a great leap from its founding years and has developed as a major constituent of innovation. The phenomenon of being "connected", the growth of emerging markets, the onset of cheaper hardware and better communication technology contributes to the proliferation of mobile technology today. However mobile industry is not just mobile phone. The industry itself is a broad range of communication devices and interconnectivity technology. Though the industry is proliferated with mobile phone manufacturers, it still evolves as it continues to create new features and new design to cater to the wide range of mobile consumer. The surfacing of "one operating system different platform" design blurred the boundary of cell phones, tablets, pocket PCs, laptops and desktop pc. Android, IOS, BB OS and Windows Mobile operates mobile phone devices that transgress its own spectrum of being just a mobile phone. The creation of fully featured mobile phone that captures images or record videos are a staple of newer mobile phones aside from its typical call and SMS capabilities. Mobile entertainment are also part of the product portfolio of mobile devices as it gives radio and music playback function, renders video and also serves as a digital reader. Lastly, mobile devices that could connect to the internet serve as the catalyst of each and every handheld device that aims to bridge the gap of communication barrier. The evolution of mobile phones is driven by the innovation that it entails. The form factor of mobile devices has shifted from its five inch thick, nine inch long, two and a half pound weight, during its early inception to its current hundred ten grams weight average, thickness average of twenty-two millimeter. The sizes also play the naming of different mobile phones, as Smartphone created new way of looking at mobile phone category, now there are phablets with average size of five inches, even tablet-phones that bears full-size tablet specification but has mobile phone capabilities. In the emergence of Smartphone, mobile application development becomes the new trend of software development. This new capability enables small and medium enterprises (SME's) to leverage technology and reach broader audience share.
What this paper intends to convey, is to look at the mobile application development industry and concentrate on the impact of various factors to ascertain penetration of mobile app project. To better create a prolific outcome, this paper utilized scenario building to a mobile app project named PetMonitor app. Scenario building will look into possible futures of the PetMonitor app and help in creating strategies for its sustained future. Lastly, the paper aims to generate a realization that this industry could be a productive source of new business model and competitive advantage. As this study derives plenty of information from the global trends, analysis of macro-environmental factors and research done by numerous publications, its intention is to come up with relevant conclusion and recommendation for the benefit of PetMonitor app's mobile environment penetration and for the mobile application industry to derive new knowledge in engaging in mobile application development. The sections of this study are as follows : Introduction, seeks to provide a background of PetMonitor app, this section will describe what the app is about. Project Scope describes the extent and boundary of the project. Review of related literature will discuss the related topics on mobile application development, the technologies identified as relevant in pursuing mobile application development and the technology foresight tool to be used as part of this paper. This section will discuss briefly the importance of these topics to ensure that the paper will provide better understanding and idea of why the proponent chose the endeavor. Theoretical framework discusses the importance of using the ten stage of scenario planning as part of ensuring sustainable advantage. This will provide the information on how PetMonitor app would be a total pet care system and a social media app for pet owners. Project methodology will discuss the process of how this paper was conducted to arrive at its conclusion and recommendation. Result of scenario planning is the discussion of the result of the ten stage scenario planning conducted in this paper. Conclusion and Recommendation is the final part of the study. This is where the proponent lists some conclusion based on the trends and analysis of the factors affecting mobile application development, and recommendation based on what were learned during the project development process.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Mobile computing